2008
DOI: 10.1007/s00228-008-0599-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacokinetics of aminoglycosides in the neonate: a review

Abstract: Background Sepsis is common in neonates and is a major cause of morbidity and mortality. Sixty percent of preterm neonates receive at least one antibiotic, and 43% of the antibiotics administered to these neonates are aminoglycosides. The clearance (Cl), serum half-life (t 1/2 ), and volume of distribution (Vd) of aminoglycosides change during the neonatal life, and the pharmacokinetics of aminoglycosides need to be studied in neonates in order to optimise therapy with these drugs. Objective The aim of this wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 59 publications
4
60
0
2
Order By: Relevance
“…We found a positive correlation between amikacin clearance and GA, as has been described for aminoglycosides (18,20,(35)(36)(37)(38)(39). The absolute value of amikacin clearance (0.61 ml/kg per min) is comparable to previously reported values (0.52 to 0.6 ml/kg per min (17)(18)(19)40). Also, the distribution volume of amikacin was similar to previously reported values of 0.58 L/kg (18) and 0.59 L/kg (17).…”
Section: Discussionsupporting
confidence: 90%
“…We found a positive correlation between amikacin clearance and GA, as has been described for aminoglycosides (18,20,(35)(36)(37)(38)(39). The absolute value of amikacin clearance (0.61 ml/kg per min) is comparable to previously reported values (0.52 to 0.6 ml/kg per min (17)(18)(19)40). Also, the distribution volume of amikacin was similar to previously reported values of 0.58 L/kg (18) and 0.59 L/kg (17).…”
Section: Discussionsupporting
confidence: 90%
“…The calculated values of the pharmacokinetic parameters (CL, Vd, t 1/2 ) for each of the patients were assessed, and they are comparable with the results of previous studies [7,[17][18][19]. Statistical difference in pharmacokinetic parameters was not detected between groups, confirming linear pharmacokinetics of gentamicin.…”
Section: Discussionsupporting
confidence: 78%
“…Compared with the adults, reduced content of fat and muscle tissues, increased percentage of body fluid (70-75% of total body weight) and an increased percentage of extracellular fluid (40% of total body weight) was observed [7,8]. Due to hydrophilic characteristics, gentamicin's volume of distribution (Vd) per kilogram of body weight is higher (some studies confirmed a two-fold increase) in the neonates compared with adults.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations